Media Advocacy in Climate Action: Showcasing Best Practices in West Africa - Binuyo, O.A.; Bamgboye, O.E.; Adeola, G.A. (Journal of Sustainability and Environmental Management, 2022)
Despite the level of threat climate change poses to humanity, climate action is poorly advocated for using one of the most powerful and easily accessible tools, the media. This stands particularly true in West Africa, the part of the planet factually concluded to be most severely affected in the case of possible climate crises. Using desktop review, this research was carried out to comb through existing literature for evidence of Africa's active advocacy for climate action through the utilization of the media. In its aim to do so, the researchers examined a total of 144 sources. 52 sources were seen to achieve best practices, based on the authors’ conceptualization of media advocacy (a measure that incorporates sustainability). Out of the sources examined, the best practices were found most in Southern Africa and least in Western Africa. Furthermore, the best media practices to carry out climate advocacy in West Africa were highlighted and explained in detail. The study contributes to the scarce literature showcasing best media practices in advocating for sustainable actions in climate adaptation with West Africa. It has the potential to open new themes and spark media discourse surrounding the drivers of sustainable climate actions in West Africa, a region with the lowest enthusiasm for climate action amongst other regions in Africa. The paper acts as a wake-up call for countries in West Africa to emulate the showcased practices in tackling climate challenges.